2011
DOI: 10.1093/nar/gkr477
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of redox sensitivity in RsrA, a zinc-containing anti-sigma factor for regulating thiol oxidative stress response

Abstract: Various environmental oxidative stresses are sensed by redox-sensitive regulators through cysteine thiol oxidation or modification. A few zinc-containing anti-sigma (ZAS) factors in actinomycetes have been reported to respond sensitively to thiol oxidation, among which RsrA from Streptomyces coelicolor is best characterized. It forms disulfide bonds upon oxidation and releases bound SigR to activate thiol oxidative stress response genes. Even though numerous ZAS proteins exist in bacteria, features that confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Upon zinc release, a disulfide bond is formed, causing a drastic conformational change in the ASF, ultimately leading to the release of the factor (52). The ZAS domain can be either redox sensitive or insensitive, which is mainly determined by the identities of the amino acid residues flanking the two conserved cysteine residues (53). In the case of the ECF48-associated ZAS domains, these flanking amino acid residues do not support redox sensing.…”
Section: Resultsmentioning
confidence: 99%
“…Upon zinc release, a disulfide bond is formed, causing a drastic conformational change in the ASF, ultimately leading to the release of the factor (52). The ZAS domain can be either redox sensitive or insensitive, which is mainly determined by the identities of the amino acid residues flanking the two conserved cysteine residues (53). In the case of the ECF48-associated ZAS domains, these flanking amino acid residues do not support redox sensing.…”
Section: Resultsmentioning
confidence: 99%
“…The zinc metal is ligated by His 37 , Cys 41 , and Cys 44 that form a characteristic HX 3 CX 2 C zinccontaining antisigma (ZAS) motif (49,76,110). Cys 11 completes the tetrahedral coordination of zinc by RsrA (110).…”
Section: Mechanisms Of Sensing Oxidative Stress By the Rsra Antisigmamentioning
confidence: 99%
“…Since zinc actually lowers the reactivity of the triggering thiolate in the finger, other determinants should activate the critical cysteine(s). The electronegative charge provided by glutamate residues flanking the HX 3 CX 2 C ZAS motif serves as an important redox determinant for the reactivity of RsrA (49). It remains to be investigated to what extent these glutamate residues influence the pKa and reactivity of the Cys 11 triggering switch.…”
Section: Activation Of Thiols In the Zinc-binding Rsra Antisigma Factormentioning
confidence: 99%
“…The response of antioxidant system was also different, for example, though ROS production can be slowed due to the absence of oxygen, a higher rate of ROS formation was also associated with the significantly higher concentrations of heavy metals (Fe, Al, Zn), a lower level of SOD was conserved in the limpet living in the heavy metals polluted area no matter hypoxia or air exposure (Weihe et al 2010). Moreover, it was also found that gene expression enable bacteria to adapt to different stresses, such as RpoE2, a gene encoding ChrR-type zinc binding anti-sigma (ZAS) factor, seems to play a crucial role in preventing and repairing the cellular damage caused by the oxidative stress in Azospirillum brasilense (Jung et al 2011;Gupta et al 2013), which could infer that low level Zn was responsible to the stimulation of antioxidant system encoded by RpoE2. Both the intracellular and extracellular protein concentration could be affected by ROS concentration, and their changes were complicated with exposure to Zn or Cefradine or Zn ?…”
Section: Effects Of Zn Concentration and Binary Exposure On Bacterialmentioning
confidence: 99%